Investigation of potential health risks in terms of arsenic in grapevine exposed to gallery waters of an abandoned mining area in Turkey - Topal, Murat; Topal, E. Isil Arslan; Obek, Erdal (Elsevier, 2020)
In this study, potential health risks in terms of arsenic in grapevine exposed to gallery waters of an abandoned mining area in Turkey were investigated. The concentrations of arsenic were determined in roots, stems, and leaves. The translocation factors and bioconcentration factors were calculated. The highest arsenic concentration in the grapevine was determined as 539.427 mg/kg, for root. The arsenic concentrations in grapevine as follows: Root>Leaf>Stem. The estimated daily exposure followed an order for the male, female, and children: dermal ingestion > inhalation > dermal. In our study, calculated carcinogenic risk values in terms of dietary, inhalation, and ingestion are higher than 10-4-10-6. As a result, the highest cancer risk on human health was determined as a dietary intake of grapevine leaves according to the calculated carcinogenic risk values. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Arsenic; Carcinogenic; Gallery water; Grapevine; Health risk